2003
DOI: 10.1080/0963828031000122203
|View full text |Cite
|
Sign up to set email alerts
|

The concerns and issues of injured workers in relation to claims/injury management and rehabilitation: the need for new operational frameworks

Abstract: On this basis some suggestions can be made for improvements to practice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
89
0
1

Year Published

2006
2006
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 104 publications
(93 citation statements)
references
References 22 publications
2
89
0
1
Order By: Relevance
“…An absence of goodwill exists among workers if they feel that managers or health care providers are not acting in their best interests and that other issues, such as cost savings and production statistics (26,29,30) and timely case closure, are an implicit priority. These conditions may undermine worker motivation to cooperate with returnto-work efforts (31,32). In turn, employers may lack motivation to commit fully to return-to-work policies when they suspect that a worker has taken advantage of an injury to reduce effort at work.…”
Section: Key Concepts and Meta-ethnographic Synthesismentioning
confidence: 99%
See 2 more Smart Citations
“…An absence of goodwill exists among workers if they feel that managers or health care providers are not acting in their best interests and that other issues, such as cost savings and production statistics (26,29,30) and timely case closure, are an implicit priority. These conditions may undermine worker motivation to cooperate with returnto-work efforts (31,32). In turn, employers may lack motivation to commit fully to return-to-work policies when they suspect that a worker has taken advantage of an injury to reduce effort at work.…”
Section: Key Concepts and Meta-ethnographic Synthesismentioning
confidence: 99%
“…Several studies found that, during the return-to-work process, injured workers experience diminished social status, feelings that they do not fit in, and a need to justify the genuineness of injury to their employers, co-workers, and friends (32). Workers also feel under scrutiny about the validity of their injuries and their entitlement to compensation and time off work (26).…”
Section: Key Concepts and Meta-ethnographic Synthesismentioning
confidence: 99%
See 1 more Smart Citation
“…In RTW processes, we also need to consider contacts with social insurance officials and employers, where the conditions for equal dialogue may be different than in healthcare, due to these actors' influence over the person's financial situation. Here, it is also relevant to refer to the person's experience of justice and recognition in the rehabilitation process, where it has been noted how perceptions of injustice, mistrust or stigmatization negatively affects the conditions for RTW [24][25][26].…”
Section: Restitution Stories Attempt To Outdistance Mortality By Rendmentioning
confidence: 99%
“…The worker is subject to the power imbalance with the system, prolonged claims and appeals processes, medical reports being used out of context, and a general lack of knowledge about rights. Claims can be manipulated by ignoring or contesting diagnoses, using confusing jargon and legalistic communication, slow payments to non-preferred physician to discourage treatment [39][40][41][42][43][44][45][46][47][48][49][50][51].…”
Section: Underreporting Of Msdsmentioning
confidence: 99%